Assessing effectiveness of regular repositioning in preventing pressure ulcers in children - Rifka Putri Andayani; Nani Nurhaeni; Dessie Wanda (MDPI AG, 2020)
Pressure ulcers have adverse effects on health. Thus, early detection of damage to skin integrity is important for preventing the occurrence of pressure sores. Meanwhile, two-hourly repositioning is a nursing intervention performed to prevent pressure ulcers. This study aimed to evaluate the implementation of regular repositioning for preventing pressure sores. The Braden Q Scale is an instrument that predicts skin breakdown caused by pressure ulcers. The designs used quasi-experiment pretest and posttest nonequivalent control group; 93 participants were selected through a nonprobability sampling technique by consecutive sampling (43 for the intervention group and 50 for the control group). Respondents in the intervention group were repositioned every 2 hours, and the control group received pressure mattress, which is done for 14 days or until the child can go home. The findings suggest that there is a significant difference in the Braden Q scores from before and after repositioning of the intervention group and the control group using pressure mattress (P<0.001). Nurses are expected to be able to detect early damage to skin integrity and to implement regular repositioning by using the Braden Q Scale.